Multilingual online resources for minority languages of a campus community - mohamad, , Nur Azmaa' Adila; Tengku Hassan, Tengku Fatin Najihah; Tengku Muda,, Tengku Norhuda; Abdul Aziz, Normaziah (Elsevier, 2011)
This paper discusses on an initiative of developing a repository on multilingual language resources for minority languages of a campus community. The choice of language is based on a survey amongst IIUM international students about the status of their mother language's resources and usages in the digital world. As a starting point, multilingual dictionaries of textual and speech for these identified languages are developed. This initiative is an effort to ensure that such minority languages will be protected from being endangered in this era of globalization.